Logistic Growth Model and Harvesting Factors - Ruly Budiono, Hafizan Juahir, Sukono, Mohamad Nurzaman, Mustafa bin Mamat, Agung Prabowo (International Journal of Advanced Science and Technology, 2020)
One of the characteristics of population growth is that it takes place very slowly in the early stages, then rises sharply and slows down as it approaches the maximum carrying capacity. Population growth models with these characteristics are called logistic models. In this article, a logistical growth model with a time-dependent environmental carrying capacity is discussed, the application of which can be applied to examples of models of seaweed growth and harvest. Furthermore, a logistic harvesting model developed with environmental carrying capacity is a function of time.